2018
DOI: 10.1021/acs.est.8b02726
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Transformations of Perfluoroalkyl Acid (PFAA) Precursors and PFAAs in Groundwater Impacted with Aqueous Film Forming Foams

Abstract: While oxidative technologies have been proposed for treatment of waters impacted by aqueous film forming foams (AFFFs), information is lacking regarding the transformation pathways for the chemical precursors to the perfluoroalkyl acids (PFAAs) typically present in such waters. This study examined the oxidative electrochemical treatment of poly- and perfluoroalkyl substances (PFASs) for two AFFF-impacted groundwaters. The bulk pseudo first order rate constant for PFOA removal was 0.23 L h A; for PFOS, this val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 28 publications
7
67
0
Order By: Relevance
“…PrePFAAs have been detected in rivers, lakes, sediments, wastewater treatment plant (WWTP) effluents, and other environments (Chen et al, 2019, Gebbink et al, 2016, Schaefer et al, 2018, Wang et al, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…PrePFAAs have been detected in rivers, lakes, sediments, wastewater treatment plant (WWTP) effluents, and other environments (Chen et al, 2019, Gebbink et al, 2016, Schaefer et al, 2018, Wang et al, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of groundwater from AFFF fire training source areas has revealed that a large fraction of the total organic fluorine remains unmeasurable via conventional analytical methods (Schaefer et al 2019). A groundwater sample from a DoD fire training source area was tested for the standard 24 PFAS analytes, total oxidizable precursors (TOPs), and also for total organic fluorine via combustion ion chromatography (TOF–CIC).…”
Section: Introductionmentioning
confidence: 99%
“…, ), electrochemical treatment (Schaefer et al. ; Soriano et al ; Schaefer et al ; Pica et al. ; Schaefer et al ), and sonolysis (Vecitis et al ; Campbell et al.…”
Section: Considerations For Available Pfas‐relevant Destruction Technmentioning
confidence: 99%
“…The first (primary) is a direct electron transfer at the surface of the anode (Zhuo et al ). This makes the anode a design parameter, with many sources suggesting that boron‐doped diamond anodes are more advantageous than mixed metal oxide anodes due to their commercial availability, high reactivity, low adsorptivity, and ability to defluorinate a wide range of PFAS (Trautmann et al ; Schaefer et al ; Soriano et al ; Schaefer et al ; Schaefer et al ). This direct electron transfer from the PFAS molecule to the anode is theorized to be a sequential defluorination process that may generate short‐chain PFAAs (Gomez‐Ruiz et al ).…”
Section: Considerations For Available Pfas‐relevant Destruction Technmentioning
confidence: 99%